Squamous Cell Carcinoma and Multiple Bowen's Disease in a Patient with a History of Consumption of Traditional Chinese Herbal Balls - Joon Seok; Kui Young Park; Kapsok Li; Beom Joon Kim; Joo Hyun Shim; Seong Jun Seo; Myeung Nam Kim; Chang Kwun Hong (Karger Publishers, 2015)
Arsenic has been classified as a class I human carcinogen, meaning that there is sufficient evidence of carcinogenicity to humans. Arsenic, however, remains a common contaminant in a number of traditional Chinese herbal balls. A 64-year-old man presented with an erythematous erosive patch on the left palm, multiple yellowish scaly patches on the right palm and an erythematous hyperkeratotic patch with bleeding on the left foot dorsum. He also had similar skin lesions on the back and buttock. He had a past medical history of chronic exposure to arsenic through consumption of traditional Chinese herbal balls. Skin biopsy revealed Bowen's disease on the left palm and squamous cell carcinoma on left foot dorsum. We report this case to emphasize that we should investigate patient's history thoroughly, including the use of Chinese herbal balls to find out arsenicism.